Strategi Pemasaran Digital dalam Mendorong Keputusan Pembelian Produk Olahan Pisang di Indonesia - Zainudin, Muhamad; Maulidah, Silvana; Riana, Fitria Dina (Image : Jurnal Riset Manajemen, 2023)
The growth of banana production in East Java faces online marketing challenges and stagnant production capacity. CV. Haza Food Indonesia needs to improve its digital marketing strategy and production efficiency as well as build consumer trust to expand the market and have a positive impact on the local economy. This research aims to explore steps to increase company production capacity, through digital marketing on purchasing decisions for processed banana products in Indonesia. Using SmartPLS 4, 201 potential consumers participated via an online questionnaire. The research results show a significant relationship between social media and purchasing decisions, as well as between eWOM and purchasing decisions. Social media also influences purchasing decisions through eWOM. These findings are consistent with previous research on the positive influence of social media and eWOM on purchasing decisions. These findings provide strategic insight for companies in optimizing digital marketing of processed banana products in the Indonesian market.